A meta-analysis comparing the outcomes of LigaSure Small Jaw versus clamp-and-tie technique or Harmonic Focus Scalpel in thyroidectomy. Issue 11 (March 2017) - Zhang, Lei; Li, Namei; Yang, Xuemei; Chen, Jie
Abstract: Background: LigaSure (LS) Small Jaw is a surgical hemostasis equipment that is newly introduced in thyroid surgery. The objective of this study is to assess the short-term efficacy and safety outcomes of LS Small Jaw compared with clamp-and-tie technique or Harmonic Focus Scalpel in thyroidectomy. Methods: A literature search was performed in the PubMed and Embase databases (until June 12, 2016) that reported the comparisons between LS Small Jaw and other techniques in thyroidectomy. Quality assessments were performed according to The Cochrane Collaboration's risk of bias tool and a modification of the Newcastle-Ottawa Scale in randomized controlled trials (RCTs) and non-RCTs, respectively. All statistical analyses were conducted using RevMan 5.3. Results: Finally, 7 studies with 813 patients were included into the meta-analysis, and all included studies were comparable with moderate-to-high quality. There was significant reduced operative time in LS Small Jaw, compared with clamp-and-tie (mean difference [MD] = −17.49, 95% confidence interval [CI]: −22.20 to 12.77, P < 0.00001) or Harmonic Focus Scalpel (MD = −2.29, 95% CI: −3.19 to 1.39, P < 0.00001). Besides, other perioperative outcomes including intraoperative blood loss and postoperative blood loss favored LS Small Jaw compared with clamp-and-tie. In terms of complications, less-temporary hypocalcemia rate was observed in LS Small Jaw compared with clamp-and-tie (odds ratio [OR] = 0.49, 95% CI: 0.27–0.90, P = 0.02), although no significant difference was detected compared with Harmonic Focus Scalpel (OR = 0.47, 95% CI: 0.14–1.56, P = 0.22). Other complications such as length of hospital stay, permanent hypocalcemia, temporary or permanent recurrent laryngeal nerve palsy, and hematomas were not significant. Conclusion: In conclusion, LS Small Jaw is more favorable than clamp-and-tie technique or Harmonic Focus Scalpel in thyroidectomy.